THE EFFECT OF CAREGIVER MALARIA PREVENTION KNOWLEDGE AND BEHAVIOR ON MALARIA RATES IN TODDLERS - Nopia Wati; Agus Ramon; Emma Rachmawati; Al. Asyary Upe; Hasan Husin; M. Amin; Oktarianita Oktarianita (Universitas Airlangga, 2020)
Background: The morbidity rate for toddlers with malaria in Indonesia had increased from 2013. Bengkulu city is a malaria-endemic area in Indonesia. Caregivers are people who stay with toddlers daily. Purpose: This study intended to identify the correlation between the malaria prevention knowledge and behavior of caregivers and malaria rates among toddlers in Basuki Rahmad Health Center in Bengkulu City. Method: This research was conducted in the Basuki Rahmad Health Center in Bengkulu City from March to April 2018. The research design was cross-sectional. The population size was 1,575 and the sample size was 127. Data were analyzed by descriptive statistics and the chi-squared test. Results: The majority of caregivers were female, with a low educational background, with good knowledge of malaria that was not reflected in their behavior. There was a relationship between knowledge of the signs and symptoms of malaria (p = 0.01), knowledge of malaria prevention practices (p = 0.01), health behaviors (p = 0.01), and use of malaria prevention practices (p = 0.01) and malaria in toddlers. Conclusion: There was a significant correlation between caregiver knowledge of the signs and symptoms of malaria, knowledge of malaria prevention practices, health service use, use of prevention practices, and malaria incidence in toddlers.